85 Years of scientific and practical activity of scientific and research institute of children’s infections - Yu. V. Lobzin; N. V. Skripchenko; V. M. Volzhanin (Журнал инфектологии)
The article represents the stages of historical development of Scientific and Research Institute of Children’s Infections from the moment of its foundation in 1927. The basic directions of scientific and practical activities are reflected. The priority of the institution and its role in the improvement of medical aid rendering to children with an infectious pathology are defined. The scientific achievements the introduction of which into practical public health service has a social value are described.